1994
DOI: 10.1055/s-2007-1007301
|View full text |Cite
|
Sign up to set email alerts
|

A 39 Year Old Man with Chronic Hepatitis

Abstract: The diagnosis of primary sclerosing cholangitis in association with autoimmune hepatitis was made in this case after the discovery of inflammatory bowel disease prompted a cholangiogram. Immunosuppressive therapy with cyclosporine prior to ERCP resulted in a significant decrease in serum aminotransferase. Liver histology and autoimmune serologies favored a diagnosis of AIH, while cholangiographic findings suggested PSC. A review of similar cases describing the simultaneous occurrence of AIH and PSC is presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…PSC-AIH overlap syndrome is an ill-defined immune-mediated disorder which is predominantly found in children, adolescents and young adults [98,[140][141][142][143][144][145][146][147][148]. Its characteristics include clinical, biochemical, and histologic features of AIH as summarized in the modified AIH score defined by an international group of experts for study purposes [62] and cholangiographic features typical of PSC [60].…”
Section: Diagnosismentioning
confidence: 99%
“…PSC-AIH overlap syndrome is an ill-defined immune-mediated disorder which is predominantly found in children, adolescents and young adults [98,[140][141][142][143][144][145][146][147][148]. Its characteristics include clinical, biochemical, and histologic features of AIH as summarized in the modified AIH score defined by an international group of experts for study purposes [62] and cholangiographic features typical of PSC [60].…”
Section: Diagnosismentioning
confidence: 99%
“…Median follow-up time was 7 (2-16) years (ASC: 6 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] vs. AIH: 8 [3][4][5][6][7][8][9][10][11][12][13][14][15]; P ϭ .17).…”
Section: Note Values Expressed As Median (Range)mentioning
confidence: 99%
“…1 An overlapping syndrome between autoimmune hepatitis (AIH) and sclerosing cholangitis has been anecdotally reported on several occasions both in children [2][3][4] and adults. [5][6][7][8] A retrospective study 4 from our Unit on 13 children with sclerosing cholangitis showed that in 40% of the cases, the clinical, biochemical, immunological, and histological presentation was indistinguishable from that of AIH. In both conditions, there was an increase in the levels of immunoglobulin G (IgG) and presence of circulating non-organ-specific nuclear (ANA) and/or smooth muscle (SMA) autoantibodies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Per AIHG guidelines, typically each disease is treated separately according to the predominant features [19]. Treatment of the overlap syndrome in the majority of cases consists of corticosteroids or combination of corticosteroids and azathioprine [4,[21][22][23][24][25][26][27][28][29][30][31].…”
Section: Overlap Syndromesmentioning
confidence: 99%